EPR Analysis on Radiation Dosimetry Material Spectra - AuthorFrida U. Ermawati (Institut Teknologi Bandung, 2001)
Radiation dosimetry work on L-α-alanine based on EPR analysis is carried out to identify radicals induced by irradiation in the system. A Varian E-12 EPR spectrometer with a rectangular parallelepiped microwave cavity to produce TE102 mode was utilized to measure first derivative absorption lines of X-band CW spectra of γ-irradiated L-α-alanine single crystals at room temperature. Six different resonance spectra measured from a number of defined crystal orientations to the magnetic field were obtained. The dominating feature of the spectrum along the <c> is a quintet with the intensity ratio close to 1:4:6:4:1. Along the and , the quintet is split into a quartet of line pairs with the intensity ratio 1:1:3:3:3:3:1:1 , accompanied by weaker resonance features. When the magnetic field is fixed on crystal planes, however, the spectrum is of superposition of two different spectra. Crystallographic and computed spectral simulation studies on the system clarified these analyses.